Longitudinal study of metacognition’s role in self-efficacy and hope development - Paweł Kleka; Hanna Brycz; Mariusz Zięba; Agnieszka Fanslau (Scientific Reports)
Abstract Self-regulation is a critical component of adaptive functioning, and individual differences in traits like metacognitive self-awareness (MCS), general self-efficacy (GSE), and hope play significant roles in influencing this ability. Self-awareness of cognitive biases is particularly relevant as it may enhance one’s capacity to manage challenges and pursue goals effectively. Prior research suggests that higher levels of MCS are associated with improved self-regulation, greater self-efficacy, and stronger hope for success. This longitudinal study sought to explore the development of self-regulation across 3 years of college education, with a specific focus on the role of MCS in shaping the trajectories of GSE and hope. Over 400 undergraduates were assessed five times throughout this period. Growth curve and causal mediation analyses were employed to examine the extent to which MCS contributed to changes in GSE and hope. Our findings indicate that self-awareness of cognitive biases (MCS) significantly influences the development of self-efficacy. Participants with higher levels of MCS exhibited a slightly faster increase in coping skills than those with lower levels. Additionally, MCS moderated the development of hope: individuals with above-median MCS scores showed a faster increase in hope, whereas those with below-median scores experienced an irregular decrease. In conclusion, MCS serves as a valuable resource for developing self-efficacy and hope. However, the influence of real-life challenges on hope appears to depend on an individual’s metacognitive skills, with better outcomes observed among those with higher MCS.